Dialogues and debates of legal and socio-legal research in Nariño (2020)
This book is divided into two thematic parts. The first addresses the most recent discussions regarding contemporary debates of law. Topics related to labor law —labor and sex workers rights— are discussed; private law —religious indoctrination—, the theory and philosophy of law —democracy, rule of law and responsibilities of the legislator—; and the relationship of law with education around peace and respect for diversity. The second part is devoted to Law and social struggles: private security policies and the monopoly of legitimate violence in the areas affected by the armed conflict; agrarian reform from a historical and economic perspective; the rights of nature; the role of ethnoeducation in the dynamics of empowerment of the indigenous and Afro-Colombian population; and the importance of sustainable development in the promotion and use of non-conventional renewable energy. The topics covered in are approached from economic, sociological, philosophical, and legal perspectives, which allows the debate about the realities of Nariñenses to be easily understood and analyzed for the different readers.